Inspired electrocatalytic performance by unique amorphous PdCu nanoparticles on black phosphorus. (1st April 2023) - Li, Weibo; Fu, Weiwei; Bai, Sitian; Huang, Heming; He, Xijun; Ma, Wenlan; Zhang, Huijuan; Wang, Yu
Abstract: The application of black phosphorus (BP) in electrocatalysis is due to its inherent susceptibility to oxidation in the presence of oxygen and water. Herein, we achieved for the first time the growth of amorphous palladium-copper alloy nanoparticles (PdCu NPs) on two-dimensional BP nanosheets by a one-step solvothermal method. PdCu NPs/BP overcomes the instability of BP and shows exceptional stability and catalytic performance for the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). In particular, PdCu NPs/BP exhibits only 4.7% decay in current density after 36, 000 s of chronoamperometric testing and 11 mV negative shift in half-wave potential after 10, 000 cycles of accelerated durability test. This has resulted in PdCu NPs/BP being the most stable among the currently known Pd-based ORR catalysts. This work introduces a novel method for growing uniform amorphous alloy nanoparticles on BP as well as new ideas for improving BP's oxidation resistance for use in electrocatalysis. Graphical abstract: Image, graphical abstract